Short (seven days) versus standard (fourteen days) oestrogen administration in a programmed frozen embryo transfer cycle: a retrospective cohort study - Wen-Jing Jiang; Jing-Yan Song; Zhen-Gao Sun (BMC, 2022)
Abstract Research question What influence does seven days of oestrogen administration versus fourteen days have on the reproductive outcomes of frozen-thawed embryo transfer (FET) in programmed endometrial preparation cycles? Design In a retrospective study, conducted at a university-affiliated tertiary hospital, a total of 2628 infertile patients (4142 FET cycles) were divided into one of two groups between January 2014 and December 2020: group A (n = 1406, seven days of oestrogen before progesterone (P4) supplementation) and group B (n = 2716, fourteen days of oestrogen before P4 supplementation). The primary outcome was cumulative live birth rate (CLBR). Secondary outcomes were other pregnancy-related outcomes, maternal and neonatal complications. Results No significant difference in CLBR was observed when comparing seven versus fourteen days of oestrogen administration before starting P4 supplementation (47.6% vs. 48.8%, P = 0.537). Furthermore, multivariable logistic regression analysis revealed that oestrogen administration in programmed FET cycles (7 days vs. 14 days) was not significantly associated with CLBR (OR 1.04, 95% CI 0.89-1.23). The risks of maternal and neonatal complications were comparable between the two groups. Conclusions Variation in the duration of oestradiol supplementation before P4 initiation does not impact FET reproductive outcomes. For infertile women who desire to conceive as soon as feasible, short (seven days) oestrogen administration in a programmed FET cycle may be a suitable alternative.